Alzheimer's and perspectives from medicinal Plants as therapeutics: a review - ANNIE JESSICA TOPPO; SHEELA CHANDRA (International Journal of Pharma and Bio Sciences, 2017)
Alzheimer’s disease is a brain disorder characterized by a progressive dementia that occurs in usually middle or late life period of an individual. There are upsurging evidences that oxidative stress is mostly responsible to the dementia. There are many drugs in the market recommended for dementia, which shows affect on diseased patients only up to minimal level, but after sometimes their suffering continues. Many drugs like Bryostatin 1, Crenezumab are there which shows promising results in clinical trials, but many shows failure after going through trials, few of them are Avagacestat, Ponezumab, etc. They also shows side effects like, indigestion, nausea, weight loss, loss of appetite and loss of strength which makes the case even worse. To rectify these activities of drugs or to avoid these, administration of secondary metabolites perhaps shows some satisfying results. Many ongoing researches on plant’s secondary metabolites like curcumin, tocopherol which are already been commercialized, shows ability to cure amyloid and tau related problems which causes dementia. Regular consumption of these nutritive substances may prevent the effects of oxidative effect on cells which causes AD.